Do Sheharon Ki Kahani - Dickens, Charles; Translated by Fazal-ul-Rehman (Lahore Fiction House, 2014)
Presents the classic tale of love, courage, and sacrifice set against the cataclysmic events of the French Revolution.
Keywords: France--Paris -- England--London -- Fathers and daughters